2017
DOI: 10.3747/co.24.3358
|View full text |Cite
|
Sign up to set email alerts
|

Guideline for Radiotherapy with Curative Intent in Patients with Early-Stage Medically Inoperable Non-Small-Cell Lung Cancer

Abstract: Objectives For this guideline, we investigated the effectiveness of radiotherapy with curative intent in medically inoperable patients with early-stage non-small-cell lung cancer (nsclc). MethodsThe guideline was developed by Cancer Care Ontario's Program in Evidence-Based Care and by the Lung Cancer Disease Site Group through a systematic review of mainly retrospective studies, expert consensus, and formal internal and external reviews. Recommendations■ Stereotactic body radiation therapy (sbrt) with curative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…Current regimens for radiation therapy employ radiation alone or concurrent with cycles of standard chemotherapy ( Das et al, 2010 ; Song et al, 2014 ). This is often limited by toxicity to normal tissues and is complicated by the development of resistance ( Anscher, 2010 ; Crinó et al, 2010 ; Eberhardt et al, 2006 ; Falkson et al, 2017 ; Howington et al, 2013 ). Although the use of targeted therapies to radiosensitize is not yet current practice, DNA repair inhibitors, for example, have been tested in preclinical models and show efficacy ( Gil del Alcazar et al, 2014 , 2016 ; Provencio and Sa´ nchez, 2014 ; Tofilon and Camphausen, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Current regimens for radiation therapy employ radiation alone or concurrent with cycles of standard chemotherapy ( Das et al, 2010 ; Song et al, 2014 ). This is often limited by toxicity to normal tissues and is complicated by the development of resistance ( Anscher, 2010 ; Crinó et al, 2010 ; Eberhardt et al, 2006 ; Falkson et al, 2017 ; Howington et al, 2013 ). Although the use of targeted therapies to radiosensitize is not yet current practice, DNA repair inhibitors, for example, have been tested in preclinical models and show efficacy ( Gil del Alcazar et al, 2014 , 2016 ; Provencio and Sa´ nchez, 2014 ; Tofilon and Camphausen, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…SBRT has evolved to become a standard option for the treatment of inoperable early stage NSCLC. It is noninvasive and mature, and most of the existing literature uses this technique[ 3 7 ]. Recently, some researchers reported that SBT is also a safe and effective modality for the treatment of inoperable early stage NSCLC[ 8 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is usually the standard option for the treatment of localized cancers, but not all patients with operable non-small cell lung cancer (NSCLC) are candidates for surgery[ 2 ]. Stereotactic body radiation therapy (SBRT), which delivers an ablative dose of radiation over a short period of time, has emerged to become a major noninvasive option for the treatment of early stage NSCLC[ 3 7 ]. This therapy is noninvasive and well-studied, and has high local control rates.…”
Section: Introductionmentioning
confidence: 99%
“…The guidelines for radiotherapy with curative intent in patients with early-stage medically inoperable NSCLC recommend BED10 ≥ 100 Gy 4) . Even in the present study, decreases in LR and RR and improvement in DSS were observed with BED10 > 100 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to surgical resection, SBRT is minimally invasive, and a complete cure can be expected. As such, it may be appropriately indicated for inoperable stage I NSCLC 4) . Furthermore, OS comparable to that achieved with surgical resection was reported in a prospective study including operable cases 5) .…”
Section: Introductionmentioning
confidence: 99%